2000
DOI: 10.1038/sj.onc.1203783
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-related proteins inhibit motility and promote growth of human malignant glioma cells

Abstract: Cellular resistance to multiple proapoptotic stimuli and invasion of surrounding brain tissue by migrating tumor cells are main obstacles to an e ective therapy for human malignant glioma. Here, we report that the Wnt family of embryonic di erentiation genes modulate growth of malignant glioma cells in vitro and in vivo and inhibit cellular migration in vitro. sFRPs (soluble Frizzled-related proteins) are soluble proteins that bind to Wnt and interfere with Wnt signaling. We ®nd that sFRP-1 and sFRP-2 are prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 43 publications
7
117
0
Order By: Relevance
“…These proteins regulate the WNT pathway by binding to WNT proteins (Ba®co et al, 1999). Importantly, SFRP1 has been shown to act as a modulator of WNT signaling (U È ren et al, 2000), and to play a role in the pathophysiology of malignant brain tumors (Roth et al, 2000). The mechanism by which SFRP1 contributes to breast cancer progression through a loss of or a reduction in mRNA expression is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins regulate the WNT pathway by binding to WNT proteins (Ba®co et al, 1999). Importantly, SFRP1 has been shown to act as a modulator of WNT signaling (U È ren et al, 2000), and to play a role in the pathophysiology of malignant brain tumors (Roth et al, 2000). The mechanism by which SFRP1 contributes to breast cancer progression through a loss of or a reduction in mRNA expression is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of SFRP1 has been associated with apoptosis (Melkonyan et al, 1997;Zhou et al, 1998), and downregulation has been found in breast tumors (Ugolini et al, 1999;Zhou et al, 1998). SFRPs ectopic expression promotes growth and inhibits motility of malignant glioma cells (Roth et al, 2000). To document the potential involvement of SFRP1 in breast cancer, we report a detailed analysis of SFRP1 expression using an in situ hybridization method that shows associations between SFRP1 lossof-expression and clinicopathological features of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The present study has demonstrated that MRP-1/CD9 and Wnt signaling play an important role in tumor progression. Therefore, new strategies, such as MRP-1/ CD9 gene therapy and soluble Frizzled-related proteins, could be rational treatments for cancer patients (Miyake et al, 2000;Roth et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This feature suggests that it may play a role as a messenger in the Wnt-signaling pathway (Kato et al, 2001). This pathway is involved in various developmental and oncogenic processes, including the positive regulation of cell cycle progression and the negative regulation of cell cycle exit by the b-catenin/ TCF pathway in neural precursors (Roth et al, 2000;Satoh and Kuroda, 2000;Megason and McMahon, 2002). To further characterize the expression profile of MARK4 in both committed neural progenitors as well as postmitotic differentiated cells, we exposed cultured neurospheres to differentiation conditions.…”
Section: Discussionmentioning
confidence: 99%